(untitled) (Balthazar, 2022)
Forty years after his death by suicide, many of us are here to remember Mario Mieli (1952-1983), his extraordinary life which abolished, as well as others, the boundaries between private and public. Starting from an interview he gave me in 1978 (re-published in this issue) and from the memory of the “gay theatre” - of which Mieli was one of the chief representative -, the author of this paper proposes to think his theatrical poetics as one of the most important and significant figure of Mieli’s biography and heritage.